PENDEKATAN PREVENTIF PETUGAS PEMASYARAKATAN DALAM REHABILITASI DAN PENCEGAHAN KRIMINALITAS BERDASARKAN PASAL 466 KUHP - Mohammad Nurdi Zen; Mulyani Rahayu (At-Tanwir Law Review, 2025)
This study seeks to assess the implementation of preventive measures by correctional officers through repressive actions toward inmates, with a focus on analyzing Article 466 of the Indonesian Penal Code (KUHP) within the framework of rehabilitation and crime prevention. Preventive approaches aim to mitigate the risk of future criminal behavior, while repressive measures are designed to deter recidivism by imposing consequences. This research adopts a qualitative methodology, utilizing data collection techniques such as literature reviews and in-depth interviews involving inmates and correctional officers. The findings reveal that the enforcement of Article 466 KUHP significantly contributes to inmate rehabilitation and crime prevention efforts, despite several challenges in its practical application. Consistent enforcement of regulations, coupled with a more humanistic approach, can help balance the protection of inmate rights with the overarching goals of rehabilitation. This study recommends enhancing the capacity of correctional officers through continuous training programs and periodic evaluations to improve the effectiveness of preventive approaches and repressive measures in reducing recidivism rates.